Optimizing Financial Management in Tanzanian Public Secondary Schools: A Case Study of Arumeru District, Tanzania - John, Wilson Daniel (Business, Management and Economics: Research Progress Vol. 2, 2024)
The main purpose of this study was to investigate the skills of the head of schools in managing unit costs for financing students in public secondary schools in the Arumeru District Council. Effective financial management is critical for optimizing the limited resources available to public schools, and the competence of school heads in handling unit costs plays a pivotal role in this regard. The study was guided by the following specific objectives: To examine how the heads of schools are familiar with the concepts of unit cost; To determine the extent to which the heads of schools are familiar with factors that affect students’ unit cost; To examine the extents head of schools are involved in the budget allocation processThe research employs a mixed-methods approach, combining quantitative surveys and qualitative interviews with school heads, teachers, and district education officers. The design used in this study is a convergent research design. The target population for this study was all heads of secondary school teachers in public schools in Meru district, Tanzania. A sample size of 30 heads of secondary schools (total sampling), 60 secondary school teachers, and 1 district education officer to provide supplementary insights in this research. The findings reveal that while some heads of schools demonstrate proficient financial management skills, others lack the necessary expertise, leading to inefficiencies in resource allocation and utilization. Also, the study revealed that the heads of schools are involved in the process of making a budget. However, the key factors influencing their financial management skills include professional training, experience, and support from district education authorities. The report emphasizes the necessity of focused professional development initiatives to improve school heads' capacity for financial management. The adoption of peer learning opportunities, ongoing training seminars, and more robust support systems from the district education offices are among the recommendations. The enhancement of educational achievements and the maintenance of sustainable funding mechanisms can be achieved by Tanzanian public secondary schools through improved resource allocation and improved financial management abilities of their school heads.